AINIDIU: An experience among university, organizations and government - Jadán-Guerrero, Janio (2013)
The influence of computer science in society is very common today, particularly in education. This article describes a report of an experience in the area of disability, and how it integrated university, organizations and government. The personal experience of the author with your SEN (Special Educational Needs) daughter allowed to create the project AINIDIU (Intelligent Agent for Children with Visual Impairment). It is a software that facilitates the interaction and integration of children with visual impairment in their educational and family environment. The paper describes the background, technological structure and assessment methodology of AINIDIU software. It also describes the diffusion and socialization phase. Finally, the technology transfer process that took place, which benefited about 1,000 visually impaired children through The Misión "Manuela Espejo", program of the Vicepresidencia de la República del Ecuador. © 2013 IEEE.